The effect of Concentration of Chitosan As Edible Coating and Storage Time on The Quality of Guava Fruits - Randi Fernando Sitorus; Terip Karo-Karo; Zulkifli Lubis (Universitas Sumatera Utara, 2014)
The aim of this research was to find the effect of concentration of chitosan and storage time on the quality of guava fruits. This research was performed in February-March 2013 at the Laboratory of Food Technology, Faculty of Agriculture, University of North Sumatera, Medan, using completely randomized design with 2 factors, i.e. : the concentration of edible coating (K) : (1%, 2%, 3% and 4%) and storage time (S) : (2 days, 4 days, 6 days and 8 days). Parameters analyzed were weight loss, moisture content, level of vitamine C, total acid, total soluble solid, total microorganism, hardness, color score, organoleptic values of color, flavor and taste. The results showed that the concentration of chitosan had highly significant effect on all parameters. Storage time had highly significant effect on all parameters. The interactions of the two factors had significant effect on weight loss and had highly significant effect on level of vitamine C, flavor and taste. The chitosan concentration of 3 % with storage time of 8 days could protect the quality of guava and was more acceptable. Keywords: chitosan concentration, guava, storage time